Antinociceptive effect of LMH-2, a new sigma-1 receptor antagonist analog of haloperidol, on the neuropathic pain of diabetic mice - Ventura-Martínez, Rosa; Ángeles-López, Guadalupe Esther; González-Ugalde, Diana; Domínguez-Páez, Tania; Navarrete-Vázquez, Gabriel; Jaimez, Ruth; Déciga-Campos, Myrna (Biomedicine & pharmacotherapy, 2024)
This study evaluates the antiallodynic and antihyperalgesic effects of LMH-2, a new haloperidol (HAL) analog that acts as sigma-1 receptor (σ1 R) antagonist, in diabetic mice using a model of neuropathic pain induced by chronic hyperglycemia. Additionally, we compared its effects with those of HAL. Hyperglycemia was induced in mice by nicotinamide-streptozotocin administration (NA-STZ, 50–130 mg/kg). Four weeks later, mechanical allodynia was assessed using the up-down method, and hyperalgesia was evoked with formalin 0.5%. We evaluated antiallodynic and antihyperalgesic effects of LMH-2 (5.6–56.2 mg/kg), HAL (0.018–0.18 mg/kg) and gabapentin (GBP, 5.6–56.2 mg/kg). The results showed that LMH-2 had a more significant antiallodynic effect compared to HAL and GBP (90.4±8.7 vs 75.1±3.1 and 41.9±2.3%, respectively; P<0.05), as well as an antihyperalgesic effect (96.3±1.2 vs 86.9±7.41 and 86.9±4.8%, respectively; P<0.05). Moreover, the antiallodynic and antihyperalgesic effect of both LMH-2 and HAL were completely abolished by PRE-084 (σ1 R agonist); and partially by pramipexole (a D2-like receptor agonist). Finally, the effect of all treatments on the rotarod test, barra, open field and exploratory behaviors showed that LMH-2 did not alter the animals' balance or the exploratory behavior, unlike as HAL or GBP. The molecular docking included indicate that LMH-2 has lower affinity to the D2R than HAL. These results provide evidence that LMH-2 exerts its antinociceptive effects as a σ1 R antagonist without the adverse effects induced by HAL or GBP. Consequently, LMH-2 can be considered a good and safe strategy for treating neuropathic pain caused by hyperglycemia in patients with diabetes. [Display omitted] •LMH-2, an analog of haloperidol, produces antinociceptive effects in diabetic mice.•Antinociceptive effect of LMH-2 is better than that produced by haloperidol or GBP.•Antiallodynic and antihyperalgesic effects of LMH-2 are due to its antagonism on σ1 R.•D2-like receptors could be partially involved in the antinociceptive effect of LMH-2.•LMH-2 did not induce extrapyramidal effects as haloperidol did.